2014
DOI: 10.1002/prot.24650
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into Pin1 peptidyl-prolylcis-transisomerization from umbrella sampling simulations

Abstract: The peptidyl-proyl isomerase Pin1 plays a key role in the regulation of phospho(p)-Ser/Thr-Pro proteins, acting as a molecular timer of the cell cycle. After recognition of these motifs, Pin1 catalyzes the rapid cis-trans isomerization of proline amide bonds of substrates, contributing to maintain the equilibrium between the two conformations. Although a great interest has arisen on this enzyme, its catalytic mechanism has long been debated. Here, the cis-trans isomerization of a model peptide system was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
4
18
0
Order By: Relevance
“…Peptide bonds connecting any amino acid with a proline residue can adopt both a cis or a trans conformation, with a weak preference for the trans conformation (99). The isomerization of misarranged peptidyl-prolyl bonds can be a rate-limiting step during protein folding (Fig.…”
Section: Protein Folding In the Ermentioning
confidence: 99%
“…Peptide bonds connecting any amino acid with a proline residue can adopt both a cis or a trans conformation, with a weak preference for the trans conformation (99). The isomerization of misarranged peptidyl-prolyl bonds can be a rate-limiting step during protein folding (Fig.…”
Section: Protein Folding In the Ermentioning
confidence: 99%
“…Another recent computational study of the catalytic mechanism of Pin1 by Di Martino et al used molecular dynamics simulations and umbrella sampling to drive the isomerization process along the peptidylprolyl dihedral angle. [99] They also showed that the bound conformational space of the substrate was much reduced. Their results suggested that the active site of Pin1 was preorganized to accommodate the substrate in a perturbed ground state conformation that positioned anamide hydrogen of the substrate to the prolyl nitrogen of the peptidylprolyl bond.…”
Section: Role Of Enzyme Dynamics In Cypacatalysismentioning
confidence: 99%
“…Dysfunctioning of Pin1 thus leads to various diseases including cancer and protein folding diseases such as Parkinson’s and Alzheimer’s. , Pin1 consists of catalytic and WW domains; while the two domains are shown to correlate with Pin1 function, , the isomerization activity is considered to be maintained solely at the catalytic domain . Pin1 reduces the free energy barrier for isomerization by ∼7 kcal/mol without any bond formation or cleavage. Yet, the molecular basis for the isomerization reaction remains elusive, and little is known about the reaction dynamics. The system thus is an ideal showcase to study the conformational transitions during the isomerizations using extensive molecular dynamics simulations.…”
mentioning
confidence: 99%
“…In this work, we study the isomerization reaction of a model ligand, Ace-Ala-pSer-Pro-Phe-Nme , (hereafter denoted as residues 164–170), catalyzed by Pin1 as well as without the enzyme from the free energy and the transition dynamics perspectives. By comparing the catalytic reaction mechanism from the two approaches in molecular detail, we are able to reveal the reaction mechanism and the fundamental role of protein conformational flexibility and dynamics in enzyme catalysis.…”
mentioning
confidence: 99%